Protective effects of Alda-1, an ALDH2 activator, on alcohol-derived DNA damage in the esophagus of human ALDH2*2 (Glu504Lys) knock-in mice. (10th May 2019) - Hirohashi, Kenshiro; Ohashi, Shinya; Amanuma, Yusuke; Nakai, Yukie; Ida, Tomomi; Baba, Kiichiro; Mitani, Yosuke; Mizumoto, Ayaka; Yamamoto, Yoshihiro; Kikuchi, Osamu; Matsubara, Junichi; Yamada, Atsushi; et al.
Abstract: Alcohol consumption is the key risk factor for the development of esophageal squamous cell carcinoma (ESCC), and acetaldehyde, a metabolite of alcohol, is an alcohol-derived major carcinogen that causes DNA damage. Aldehyde dehydrogenase2 (ALDH2) is an enzyme that detoxifies acetaldehyde, and its activity is reduced by ALDH2 gene polymorphism. Reduction in ALDH2 activity increases blood, salivary and breath acetaldehyde levels after alcohol intake, and it is deeply associated with the development of ESCC. Heavy alcohol consumption in individuals with ALDH2 gene polymorphism significantly elevates the risk of ESCC; however, effective prevention has not been established yet. In this study, we investigated the protective effects of Alda-1, a small molecule ALDH2 activator, on alcohol-mediated esophageal DNA damage. Here, we generated novel genetically engineered knock-in mice that express the human ALDH2*1 (wild-type allele) or ALDH2*2 gene (mutant allele). Those mice were crossed, and human ALDH2*1/*1, ALDH2*1/*2 and ALDH2*2/*2 knock-in mice were established. They were given 10% ethanol for 7 days in the presence or absence of Alda-1, and we measured the levels of esophageal DNA damage, represented by DNA adduct ( N 2 -ethylidene-2′-deoxyguanosine). Alda-1 significantly increased hepatic ALDH2 activity both in human ALDH2*1/*2 and/or ALDH2*2/*2 knock-in mice and reduced esophageal DNA damage levels after alcohol drinking. Conversely, cyanamide, an ALDH2-inhibitor, significantly exacerbated esophageal DNA adduct level in C57BL/6N mice induced by alcohol drinking. These results indicate the protective effects of ALDH2 activation by Alda-1 on esophageal DNA damage levels in individuals with ALDH2 gene polymorphism, providing a new insight into acetaldehyde-mediated esophageal carcinogenesis and prevention. Abstract : We generated human ALDH2*2 (Glu504Lys) knock-in mice and showed the protective effects of Alda-1 (ALDH2 activator) on esophageal DNA damage in those mice with alcohol drinking. Our findings can be the basis for developing a novel prevention for alcohol-mediated esophageal carcinogenesis.